Effects of dilution on the hardness and residual stresses in multipass steel weldments. (November 2020) - Sun, Y.L.; Hamelin, C.J.; Vasileiou, A.N.; Xiong, Q.; Flint, T.F.; Obasi, G.; Francis, J.A.; Smith, M.C.
Abstract: A thermal-metallurgical-mechanical model was developed to study the effects of dilution in each weld pass for multipass gas tungsten arc and submerged arc welding in low alloy steel (i.e. SA508) plates. Hardness distributions and residual stresses were measured on the transverse sections perpendicular to the welding direction of the manufactured weldments. The predicted hardness and residual stresses were compared with the measurement data and shown to be reasonably accurate. The results showed that dilution can significantly affect both the hardness and the residual stress field in the weld metal. It was found that, for the base and filler materials used, increased dilution led to greater weld-metal hardness and reduced the magnitude of tensile stress or promoted compressive stress in the as-deposited and reheated weld metals. This mechanical behaviour is associated with the tendency for diluted weld metal to experience delayed austenite decomposition, owing to the high hardenability of SA508 steel relative to the filler materials used. Although dilution is irrelevant for the hardness of the base material and its transformation products adjacent to the weld metal, it affected the full-field residual stresses via the equilibrium interaction between the stresses in the base and weld metals. Highlights: Dilution effect is investigated for multipass arc welds with base material having higher hardenability than filler material. Predictions of hardness and residual stresses are in reasonable agreement with measurements. Higher dilution leads to higher hardness of the studied weld metal in both as-deposited and reheated states. Higher dilution reduces tensile stress or promotes compressive stress in the as-deposited and reheated weld metals.